A Decision Support System for Selecting the Optimal Specialization Using the Analytical Hierarchy Process (AHP) - Hamsiah, Hamsiah; Putri, Nurapni Jami; Irma Rosi, Adek (The Future of Education Journal, 2026)
The selection of a study specialization is an important decision for students, as it influences the development of academic competencies and future career paths. However, the process of choosing a specialization is often conducted subjectively and does not systematically consider multiple criteria. This study aims to design and implement a Decision Support System (DSS) for selecting a study specialization using the Analytical Hierarchy Process (AHP) method. The AHP method is applied to address multicriteria decision-making problems by constructing a hierarchical structure, performing pairwise comparisons among criteria, and determining the priority weights of each alternative. The criteria used in this study include academic performance, career prospects, and the quality of supporting lecturers. The results indicate that the application of the AHP method is able to provide objective and consistent recommendations for study specializations based on the highest priority values. Thus, the developed decision support system can assist students in determining the study specialization that best aligns with their abilities and interests.